Fostering Physician Trust: The Critical Role of Explainable AI in Clinical Decision Making - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The integration of Artificial Intelligence AI into healthcare has ushered in an era of unprecedented diagnostic and prognostic power. Modern AI models, parti...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care